A Novel Fat Making Strategy With Adipose-Derived Progenitor Cell-Enriched Fat Improves Fat Graft Survival. (8th May 2021) - Fan, Pengju; Fang, Man; Li, Jingjing; Solari, Mario G; Wu, Dingyu; Tan, Wuyuan; Wang, Yongjie; Yang, Xinghua; Lei, Shaorong
Abstract: Background: A low survival rate is one of the main challenges in fat grafting. Objectives: This study aimed to evaluate whether microfat obtained by a novel strategy promoted the survival and retention of fat grafts. Methods: A 5-mm-diameter blunt tip cannula with large side holes ( 30 mm 2 /hole) was used to obtain macrofat. A novel strategy based on a newly invented extracorporeal cutting device was then used to cut the macrofat into microfat, which was named adipose-derived progenitor cell enrichment fat (AER fat); Coleman fat was used as the control. Aliquots (0.5 mL) of both types of fat were transplanted into 10 nude mice and analyzed 10 weeks later. Western blotting, flow cytometry, and immunofluorescence were performed to assess the AER fat characteristics and underlying mechanisms. Results: The retention rate of fat grafts in AER fat–treated animals was significantly higher than that in the Coleman group (mean [standard deviation] 54.6% [13%] vs 34.8% [9%]; P < 0.05) after 10 weeks. AER fat contained more dipeptidyl peptidase-4–expressing progenitor cells (3.3 [0.61] × 10 3 vs 2.0 [0.46] × 10 3 cells/mL; P < 0.05), adipose-derived plastic-adherent cells (6.0 [1.10] × 10 4 vs 2.6 [0.17] × 10 4 cells/mL; P < 0.001), and viable adipocytes than Coleman fat. Moreover, histologic analysis showed that AER fat grafts had better histologic structure and higher capillary density. Conclusions: AER fat transplantation is a potential strategy to improve the survival and long-term retention of fat grafts. AER fat contained more dipeptidyl peptidase-4–expressing progenitor cells.